Implementasi Kebijakan Pengelolaan Sampah di Dinas Lingkungan Hidup Kota Cimahi - Supriatna, Cecep; Susniwati, Susniwati; Wiradiputra, Indra Aldila (Universitas Batanghari Jambi, 2024)
The purpose of this study is to find out the implementation of waste management policies at the Cimahi City Environment Agency (DLH) using a qualitative method with a descriptive nature. Data was collected by observation, documentation and interview techniques. Based on the research conducted, it can be concluded that (1) the implementation of waste management policies in Cimahi DLH City has been carried out properly in accordance with Cimahi City Regional Regulation No. 6/2019. However, not all of it can be carried out effectively because not all waste at the TPS can be transported to the TPA every day, this is due to weather factors, infrastructure and inadequate infrastructure. (2) The lack of human resources at DLH Cimahi City is due to the limited recruitment of employees according to staffing regulations. To overcome this, employee training is carried out; (3) Implementation of waste management policies carried out by DLH Cimahi City, namely the Maggotization program, namely the decomposition of organic waste by utilizing maggot larvae and several ways of managing waste, namely through the Cimahi People's Movement to Sort Waste (Gerak Ompipah) and also Together Reducing Waste (Barengas) ; (4) The strategy for disseminating information on the application of waste management policies in Cimahi City is carried out through education and outreach from DLH Cimahi directly to the public.